Quantifying rival bond fission probabilities following photoexcitation: C–S bond fission in t-butylmethylsulfide. Issue 20 (29th April 2019) - Bain, Matthew; Hansen, Christopher S.; Karsili, Tolga N. V.; Ashfold, Michael N. R.
Abstract : Competitive bond fission probabilities in a photoexcited molecule are quantified using contemporary ion imaging methods. Abstract : We illustrate a new, collision-free experimental strategy that allows determination of the absolute probabilities of rival bond fission processes in a photoexcited molecule – here t -butylmethylsulfide (BSM). The method combines single photon ('universal') ionization laser probe methods, simultaneous imaging of all probed fragments (multi-mass ion imaging) and the use of an appropriate internal calibrant (here dimethylsulfide). Image analysis allows quantification of the dynamics of the rival B–SM and BS–M bond fission processes following ultraviolet (UV) excitation of BSM and shows the former to be twice as probable, despite the only modest (∼2%) differences in the respective ground state equilibrium C–S bond lengths or bond strengths. Rationalising this finding should provide a stringent test of the two close-lying, coupled excited states of 1 A′′ symmetry accessed by UV excitation in BSM and related thioethers, of the respective transition dipole moment surfaces, and of the geometry dependent non-adiabatic couplings that enable the rival C–S bond fissions.